Correlation study of metformin drug with vit.B12 and folic acid in women suffer of type 2 diabetic disease (Journal of Pharmaceutical Negative Results, 2022)
Background: Diabetes mellitus is the most well-known endocrine disorder to date. Year after year, the prevalence of type 2 diabetes (T2D), which accounts for more than 90% of all diabetes cases, rises fast. Metformin is the most generally prescribed oral diabetes medication, and it is used to treat all diabetics worldwide in combination with diet and exercise. Though evidence shows that using metformin for a long time might cause vitamin B12 and folic acid deficiency, only a few studies have done in this regard. Materials and methods: Participants were divided into two groups: diabetic females (MET) (n = 60) and healthy control females (n = 25). All diabetic patients receiving Metformin (500 mg twice daily) were further divided into two groups based on treatment duration: less than 2 years and more than 2 years. Serum vitamin B12, folic acid, T3 and T4 levels were tested in the subjects. Results: the level of serum Folic acid in diabetic females with duration of metformin treatment more than 2 years was (77.05 ± 2.61), while its level in diabetic females with duration of metformin less than 2 years was (130.55 ± 1.86) both were significantly lower (p<0.001) than its level in healthy control (426.47 ± 32.51). Student’s t-test demonstrated a very significant drop in blood folic acid levels in diabetic females who had used metformin for more than 2 years compared to females who had used metformin for less than 2 years. Conclustion : To determine the risk of B12 and B9 deficiency in Diabetes females taking metformin, compared to the healthy control group.